2014
DOI: 10.1186/1472-6920-14-136
|View full text |Cite
|
Sign up to set email alerts
|

Online training course on critical appraisal for nurses: adaptation and assessment

Abstract: BackgroundResearch is an essential activity for improving quality and efficiency in healthcare. The objective of this study was to train nurses from the public Basque Health Service (Osakidetza) in critical appraisal, promoting continuous training and the use of research in clinical practice.MethodsThis was a prospective pre-post test study. The InfoCritique course on critical appraisal was translated and adapted. A sample of 50 nurses and 3 tutors was recruited. Educational strategies and assessment instrumen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
36
0

Year Published

2015
2015
2020
2020

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 26 publications
(38 citation statements)
references
References 30 publications
2
36
0
Order By: Relevance
“…Among published studies on EBP courses for nurses, some did not yield conclusive results (Mollon et al, 2012;Sherriff, Wallis, & Chaboyer, 2007), some did not include a control group (Kim et al, 2013;Varnell, Haas, Duke, & Hudson, 2008), and some used instruments with no established psychometric validity to measure EBP competence (Reviriego et al, 2014). However, other studies have offered more consistent results on factors that facilitate EBP learning, including a higher nurse educational level (Hart et al, 2008), the presence of EBP mentors or leaders with EBP expertise (Wallen et al, 2010), and the promotion of student self-learning (Zadvinskis, 2008).…”
Section: Review Of Literaturementioning
confidence: 99%
See 1 more Smart Citation
“…Among published studies on EBP courses for nurses, some did not yield conclusive results (Mollon et al, 2012;Sherriff, Wallis, & Chaboyer, 2007), some did not include a control group (Kim et al, 2013;Varnell, Haas, Duke, & Hudson, 2008), and some used instruments with no established psychometric validity to measure EBP competence (Reviriego et al, 2014). However, other studies have offered more consistent results on factors that facilitate EBP learning, including a higher nurse educational level (Hart et al, 2008), the presence of EBP mentors or leaders with EBP expertise (Wallen et al, 2010), and the promotion of student self-learning (Zadvinskis, 2008).…”
Section: Review Of Literaturementioning
confidence: 99%
“…EBP knowledge and skills in nurses have been improved by educational interventions with different durations and methodologies, including online self-learning courses (Hart et al, 2008;Reviriego et al, 2014), courses within a tutoring program (Kim et al, 2013), and face-to-face courses with a "workshop" format, although these only improved skills in the search for evidence (Sherriff et al, 2007). In contrast, EBP knowledge and skills were not improved by an exclusively online educational intervention (Mollon et al, 2012), which may be attributable to the lack of student feedback or learning assessment.…”
Section: Intervention Group (Ebp) Comparison Group (Digital Resources)mentioning
confidence: 99%
“…Several studies have found a connection between the use of EBP and nurses' knowledge and skills [34,36] and have shown that nurses' knowledge and skills improve after educational interventions. [37][38][39] However, it has been difficult to prove the appropriate form and content of such education. [36] Mentorship and continuing education are often pointed to as successful strategies.…”
Section: Discussionmentioning
confidence: 99%
“…The translation process is related to autonomous decisions about how knowledge can be used to improve results; how to negotiate relations in health system [individuals, team, internal and external relations] and how to conquer resources to sustain changes/improvements in practice [16]. It emphasizes that research is an essential activity for the advancement of health sciences and research results should contribute to improving the quality and efficiency of health organizations [17].…”
Section: Discussionmentioning
confidence: 99%